Distributed systems : an algorithmic approach - Ghosh, Sukumar (Boca Raton, Florida : CRC Press, 2015)
This text presents the material in a clear and straightforward manner, making it accessible to undergraduate students while still maintaining value for experts.
Section I. Background materials -- Chapter 1. Introduction -- Chapter 2. Inter process communication : an overview -- Section II. Foundations topics -- Chapter 3. Model for communication -- Chapter 4. Representing distributed algorithms : syntax and semantics -- Chapter 5. Program correctness -- Chapter 6. Time in a distributed system -- Section III. Important paradigms -- Chapter 7. Mutual exclusion -- Chapter 8. Distributed snapshot -- Chapter 9. Global state collection -- Chapter 10. Graph algorithms -- Chapter 11. Coordination algorithms -- Section IV. Faults and fault-tolerant systems -- Chapter 12. Fault-tolerant systems -- Chapter 13. Distributed consensus -- Chapter 14. Distributed transactions -- Chapter 15. Group communication -- Chapter 16. Replicated data management -- Chapter 17. Self-stabilizing system -- Section V : Real-world issues -- Chapter 18. Distributed discrete-event simulation -- Chapter 19. Security in distributed systems -- Chapter 20. Sensor networks -- Chapter 21. Social and peer-to-peer networks.
Includes bibliographical references and index.
Keywords: SOFTWARE ARCHITECTURE